2000
DOI: 10.1002/1522-2675(20001108)83:11<3043::aid-hlca3043>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Photomodulable Materials. Synthesis and Properties of Photochromic 3H-Naphtho[2,1-b]pyrans Linked to Thiophene Unitsvia an Acetylenic Junction

Abstract: The synthesis of 3H-naphtho[2,1-b]pyrans linked to mono-, di-, or terthiophene via an acetylenic junction is described (Schemes 2 and 3). The synthetic approaches involve successive Sonogashira coupling reactions. The photochromic properties in solution of these novel materials were investigated under continuous irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 20 publications
6
29
0
Order By: Relevance
“…16,17 Mono bromobithiophene and monobromoterthiophene were prepared according to the literature. [18][19][20][21] 2,2-Bithiophene (BT) (Aldrich) was purified through vacuum sublimation. The supporting electrolyte for electrochemical measurements was tetrabutylammonium hexafluorophosphate, Bu 4 NPF 6 (SigmaAldrich, 98 % purity, reagent grade), which was stored in a vacuum dessicator over silica gel.…”
Section: Methodsmentioning
confidence: 99%
“…16,17 Mono bromobithiophene and monobromoterthiophene were prepared according to the literature. [18][19][20][21] 2,2-Bithiophene (BT) (Aldrich) was purified through vacuum sublimation. The supporting electrolyte for electrochemical measurements was tetrabutylammonium hexafluorophosphate, Bu 4 NPF 6 (SigmaAldrich, 98 % purity, reagent grade), which was stored in a vacuum dessicator over silica gel.…”
Section: Methodsmentioning
confidence: 99%
“…Chemicals. The (NPA) 2 T was prepared for previous works (10,11). Its purity was checked by high-performance liquid chromatography (.98%), using a diode array detector.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that it exhibits a classical photochromic behavior because the starting closed form yields the open (photomerocyanine type) colored form, PM (k max at ;480 nm in toluene) by thermally reversible photocleavage of the C-O bond. A bleaching rate constant of 0.14 s ÿ1 for the thermal back reaction in toluene at 293 K has been reported (10). The compound was also found to exhibit a significant fluorescence emission (11).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Nowadays, these photochromic compounds are also used in architecture, automotive industry, cosmetics, textiles, decoration, etc [8][9][10][11][12]. Most of the scientific research done on photochromic C. R. Chimie 13 (2010) [212][213][214][215][216][217][218][219][220][221][222][223][224][225][226] NP compounds was devoted to the optimization of its spectral and kinetic properties by substitution of functional groups in the photochromic molecule [13][14][15][16][17][18][19][20][21]. The most remarked properties of these materials, such as the absorption spectra upon irradiation with UV light and the kinetic of the bleaching process (recovery of original whiteness) have been measured in different solvents [4,[22][23][24] or dispersed in organic polymer matrices [7,21,25].…”
Section: Introductionmentioning
confidence: 99%